Estudio de las redes privadas virtuales VPN para soporte a usuarios remotos del sistema informático del cuerpo de bomberos de la ciudad de Montalvo. - Martínez Chang, Yuley Yessenia (2017)
As time passes, technology is evolving more and more, for this reason has seen the need to create, develop and implement new computer systems, to ensure that information transmitted by different channels are safe, due to the importance of information. On the other hand, networks today have been the key point of insecurity, that malicious people want to have access to information that is not their responsibility, networks have reduced costs and time to companies to a great advantage for organizations. For this reason the Ciudad Montalvo Fire Department has implemented the VPN (Virtual Private Network) connection, so that the information travels safely to its destination, the problems currently presented by the VPN within the Institution are that the staff of the institution can not access the network from smartphones or laptops. Another problem that has manifested itself is that according to the change that was presented within the Fire Department of the Montalvo City, to be autonomous happened to be municipal, and there was an obligation to make change of internet service provider doing this that the VPN stops functioning, because the new provider does not offer public IPs causing annoyance when running the VPN.